The Growth Response of Gmelina arborea Roxb. by Growth Stimulant at Nursery Permanen Dramaga IPB RESPON PERTUMBUHAN BIBIT Gmelina arborea ROXB TERHADAP PENAMBAHAN Growth Stimulant DI PERSEMAIAN PERMANEN IPB - Arif Irwansyah; Yadi Setiadi; Basuki Wasis; Noor Faiqoh Mardatin (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
The objective of this research was to study the growth response of G. arborea seedling with growth stimulant at nursery seedling area. Three months of age seedlings were selected and used. The research was conducted three concentrations of BioNature-50 in completely randomized design with 3 replications.. The best results for G. arborea was reached on GSA-1 (1,21 liter BioNature-50 dissolved into 15 liter water). The parameter on plant such as height, stem diameter, and shoot root ratio were significantly affected.Key words: BioNature-50, concentration